2023
DOI: 10.3389/fnut.2023.1052281
|View full text |Cite
|
Sign up to set email alerts
|

Extra cup of tea intake associated with increased risk of Alzheimer’s disease: Genetic insights from Mendelian randomization

Abstract: BackgroundObservational studies report inconclusive effects of tea consumption on the risk of Alzheimer’s disease (AD), and the mechanisms are unclear. This study aims to investigate the effects of genetically predicted tea intake (cups of tea consumed per day) on AD, brain volume, and cerebral small vessel disease (CSVD) using the two-sample Mendelian randomization (MR) method.MethodsSummary statistics of tea intake were obtained from UK Biobank (N = 447,485), and AD was from the International Genomics of Alz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Moreover, a meta-analysis of prospective studies revealed that the tea could be inversely associated with neurodegenerative disorders ( 43 ), which was also consistent with our results. Conversely, a MR study genetically suggested a potential causal link between increased tea intake and elevated AD risk, with genetically predicted tea intake associated with decreased brain volume, particularly in the gray matter and right hippocampus ( 44 ). Finally, a dose–response meta-analysis indicated an inverse association between tea consumption and cognitive disorders, suggesting 1 cup/day of tea intake leads to an 11% reduction in cognitive deficits ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a meta-analysis of prospective studies revealed that the tea could be inversely associated with neurodegenerative disorders ( 43 ), which was also consistent with our results. Conversely, a MR study genetically suggested a potential causal link between increased tea intake and elevated AD risk, with genetically predicted tea intake associated with decreased brain volume, particularly in the gray matter and right hippocampus ( 44 ). Finally, a dose–response meta-analysis indicated an inverse association between tea consumption and cognitive disorders, suggesting 1 cup/day of tea intake leads to an 11% reduction in cognitive deficits ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most previous studies suggested that tea had protective effects on aging (Feng et al, 2021 ; Zhang et al, 2021 ). However, some studies have found that excess tea intake has an adverse impact on cognition and is associated with Alzheimer's disease (Hu et al, 2022 ; Sun et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tea stands out as a ubiquitous beverage that has garnered substantial attention due to its potential health-enhancing properties [ 13 ]. Rich in caffeine and tea polyphenols [ 14 ], the advantageous attributes of tea are primarily ascribed to its robust polyphenol content, particularly catechin, renowned for its potent antioxidant capabilities [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of its variety, tea and its derivatives exhibit a spectrum of effects, including antibacterial qualities [ 15 ], anti-inflammatory attributes [ 16 ], antitumor potential [ 17 ], antiviral properties [ 18 ], and more. The documented ability of catechin's polyphenols to impede amyloid-beta aggregation and exhibit anti-apoptotic effects suggests a potentially substantial protective role against AD [ 13 , 14 ]. The presence of theanine in tea appears to correlate with improvements in cognitive function [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%